Intelligent Smart Tourism Education: some experiments with AI based Learning for Cultural Tourism - Fasolo, Michele (Archeomatica, 2024)
The paper discusses the integration of artificial intelligence (AI) in education, particularly focusing on digital tourism. It highlights the use of AI-assisted learning to personalize educational content and enhance learning experiences for students. Specific examples include AI-powered platforms for designing cultural travel blogs and personalized learning paths for cultural tourism education. The paper also emphasizes the role of AI in supporting self-learning, adaptive learning systems, intelligent tutoring systems, and natural language processing. It showcases case studies from the University of Rome "Tor Vergata" and explores AI's potential to improve accessibility and provide tailored educational experiences for learners with disabilities.